188k views
5 votes
3.1 Factorise completely

3.1.2 3x2 - 2x - 8​

2 Answers

3 votes

Answer:

3x² – 2x – 8

=> 3x² – 6x + 4x – 8

=> 3x( x – 2 ) + 4( x – 2 )

=> ( 3x + 4 ) ( x – 2 )

Therefore,

Either, 3x + 4 = 0

3x = - 4

x = - 4/3 (Ans)

And,

x – 2 = 0

x = 2 (Ans)

User Yiannr
by
4.8k points
1 vote

Answer:

(x - 2)(3x + 4)

Explanation:

Given

3x² - 2x - 8

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 3 × - 8 = - 24 and sum = - 2

The factors are - 6 and + 4

Use these factors to split the x- term

3x² - 6x + 4x - 8 ( factor the first/second and third/fourth terms )

= 3x(x - 2) + 4(x - 2) ← factor out (x - 2) from each term

= (x - 2)(3x + 4)

User DreamWerx
by
5.1k points